The Influence of Customer Experience, Price Perception and Word of Mouth on Purchasing Decisions - Maya Angelica Lamtiur Sihombing Sihombing; Surono (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the effect of Customer Experience, Price Perception, and Word of Mouth on purchasing decisions at Angel Kebaya. Using a quantitative approach, data was collected through a survey with 150 respondents selected by purposive sampling. The questionnaire was distributed via Google Form in January 2025. The results showed that customer experience, price perception, and word of mouth have a significant influence on purchasing decisions. This research expands the understanding of how these three factors influence purchasing decisions. The findings provide insights for Angel Kebaya to improve customer experience, set competitive prices, and encourage positive word of mouth.